Evaluating consumer self-medication practices, pharmaceutical care services, and pharmacy selection: a quantitative study - Lusine Nazaryan; Anush Barseghyan; Maria Rayisyan; Margarit Beglaryan; Marta Simonyan (BMC, 2024)
Abstract Background The primary objectives of this study were the evaluation of consumer self-medication practices, the assessment of pharmaceutical care provided by pharmacy employees, and the analysis of consumer satisfaction with such care. The research was also aimed at examining the main criteria that consumers consider important when selecting a pharmacy in Armenia. Methods The survey was based on an anonymous questionnaire and carried out between March 2020 and November 2021. It was aimed at providing a comprehensive assessment of pharmaceutical care services and consumer pharmacy choice by investigating two distinct groups: pharmacy consumers and pharmacy employees. Results The research reveals that many residents in Armenia engage in self-medication without consulting professional sources, which can lead to potential risks and result in dangerous consequences. This is partly due to a lack of trust in pharmacy employees, which is primarily due to their inability to provide adequate information and advice. This study highlights a significant need for improvement in the quality of service provided by pharmacy employees. Despite these challenges, the majority of consumers reported having a preferred pharmacy, and that employee knowledge is the most important criterion when choosing a pharmacy. Conclusions Consumer distrust, in this context, is based on the incomplete knowledge or incompetency of pharmacy employees. Collective actions should be taken to improve the role of pharmacy employees and consequently improve the public trust in them, which can ensure better control of self-medication and reduce the instances of mistreatment.